2019
DOI: 10.1371/journal.pone.0222653
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 full agonism exerts feeding suppression and weight loss through afferent vagal nerve

Abstract: GPR40/FFAR1 is a Gq protein-coupled receptor expressed in pancreatic β cells and enteroendocrine cells, and mediates insulin and incretin secretion to regulate feeding behavior. Several GPR40 full agonists have been reported to reduce food intake in rodents by regulating gut hormone secretion in addition to their potent glucose-lowering effects; however, detailed mechanisms of feeding suppression are still unknown. In the present study, we characterized T-3601386, a novel compound with potent full agonistic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Our finding is in line with previous observations where peripheral administration of CCK or GLP‐1 (in the fed state) had no effect on food intake in the SAPCCK model 22 . A recent study investigated the effect of T‐3601386, a synthetic FFA1 receptor agonist, and robust GLP‐1 stimulator, on food intake 49 . T‐3601386 robustly stimulated GLP‐1 secretion in mice, 49 suggesting that the compound can stimulate both Gq and Gs cascades, 39 and presumably stimulate CCK secretion as well.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is in line with previous observations where peripheral administration of CCK or GLP‐1 (in the fed state) had no effect on food intake in the SAPCCK model 22 . A recent study investigated the effect of T‐3601386, a synthetic FFA1 receptor agonist, and robust GLP‐1 stimulator, on food intake 49 . T‐3601386 robustly stimulated GLP‐1 secretion in mice, 49 suggesting that the compound can stimulate both Gq and Gs cascades, 39 and presumably stimulate CCK secretion as well.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been demonstrated that activation of the free fatty acid receptor 1 (FFAR1, a.k.a. G proteincoupled receptor 40) in the enterocytes plays an important role in reducing appetite in rodents [129]. The FFAR1 is activated by LCFA in monogastrics [130] and ruminants [131].…”
Section: Inhibition Of Feed Intake By Dietary Fa: Possible Role Of Enmentioning
confidence: 99%
“…On the other hand, we cannot also deny the influence of indirect GLP-1 secretion via C10:0-stimulated GPR84 activation by neuronal or immune cells. For example, vagal afferent activation indirectly promotes GLP-1 secretion ( 28 ), and GPR40 stimulation also promotes GLP-1 secretion via the afferent vagal nerve ( 29 ). Further studies using tissue-specific GPR84-deficient mice, or GPR40 and GPR40/GPR84 double-deficient mice are needed to clarify these problems.…”
Section: Discussionmentioning
confidence: 99%